2013
DOI: 10.19030/jabr.v29i6.8206
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital In Mexican SMEs From The Perspective Of The Resource-Based And Dynamic Capabilities Views

Abstract: <p>This paper combines the resource-based and dynamic capabilities views to examine intellectual capital in Mexican small and medium enterprises (SMEs) and its relation to competitive advantage. Following an exploratory approach, this paper relies on face-to-face interviews with managers to take an in-depth look at the three components of intellectual capital: human, organizational, and relational capital. Further, a SME typology is proposed and the examined companies are categorized accordingly. Dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(63 reference statements)
1
18
0
1
Order By: Relevance
“…The results indicate that human capital (H1) and relational capital (H3) have significant positive relationships with performance, while structural capital (H2) was found to be a non-significant driver of firm performance. The significant effect of human capital on firm performance is consistent with prior studies of Daou et al (2013), Khalique and Pablos (2015), and Tovstiga and Tulugurova (2007). The results are also in agreement with Alipour (2012) and Morariu (2014), who found the significant role of human capital in assisting firms to achieve superior performance.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…The results indicate that human capital (H1) and relational capital (H3) have significant positive relationships with performance, while structural capital (H2) was found to be a non-significant driver of firm performance. The significant effect of human capital on firm performance is consistent with prior studies of Daou et al (2013), Khalique and Pablos (2015), and Tovstiga and Tulugurova (2007). The results are also in agreement with Alipour (2012) and Morariu (2014), who found the significant role of human capital in assisting firms to achieve superior performance.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Prior empirical studies found that the reliance on intellectual capital offers firms a number of positive outcomes such as competitive advantages, enhancing corporate values, and firm effectiveness (Kamaluddin & Abdul Rahman, 2009). The impact of knowledge economy that emphasises intellectual capital is stronger for SMEs than larger firms considering the higher contribution of SMEs in the nation's economic development yet operating within scarce resources, which might hamper them from continuously serving the role as the economic backbone (Daou, Karuranga, & Su, 2013) https: //dx.doi.org/10.15405/epsbs.2018.07.02.41 Corresponding Author: Salwa Muda Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 384…”
Section: Introductionmentioning
confidence: 99%
“…interesting conclusions from the perspective of intellectual capital seen as part of the company's dynamic capacity based on strategic resources. Although the study has been conducted in Mexico, its results can be valid in other emerging economies (Daou, Karuranga and Su, 2013):…”
Section: Bioeconomy Development and Using Of Intellectual Capital Formentioning
confidence: 99%
“…From the results of Ngah & Ibrahim's research (2009), it is known that intellectual capital in SMEs could contribute to the product innovation process that encourages SMEs performance improvement. In line with Daou et al (2013) in general intellectual capital has a positive impact on the performance of SMEs.…”
Section: Introductionmentioning
confidence: 66%